Considerations for the Design of a Central Counterparty for the Mexican Money Market - de Lascurain M., Miguel (2011)
The financial crisis has brought the problems of regulatory failure and unbridled counterparty risk to the forefront in financial discussions. In the last decade, central counterparties have been created in order to face those insidious problems. In Mexico, both the stock and the derivatives markets have central counterparties, but the money market has not. This paper addresses the issue of creating a central counterparty for the Mexican money market. Recommendations that must be followed in the design and the management of risk of a central counterparty, given by international regulatory institutions, are presented in this study. Also, two different conceptual designs for a central counterparty, appropriate for the Mexican market, are proposed. Final conclusions support the creation of a new central counterparty for the Mexican money market